4CPS-262 A novel artificial intelligence-based tool to assess anticholinergic burden: a survey. Issue 1 (23rd March 2023) - Secchi, A; Fox, C; Mamayusupova, H; Sami, S; Maidment, I; Coulton, S; Myint, PK; Fox, C
Abstract : Background and Importance: Many medications possess anticholinergic activity. Their use is associated with a number of serious adverse effects including cognitive effects. The cumulative anticholinergic effect of medications as assessed by tools such as the anticholinergic burden scale (AchB) can identify people particularly at risk of anticholinergic side-effects. Currently, more than 20 tools are available for clinicians to use, but there is no consensus on the most appropriate tool. Aim and Objectives: To assess the overall need for an assessment tool as well as the usability of a newly created tool, the International Anticholinergic Cognitive Burden Tool (IACT), to assess anticholinergic burden of medications. Material and Methods: A newly created online tool, International Anticholinergic Cognitive Burden Tool (IACT), based on natural language processing and chemical structure analysis, was developed and made available for clinicians to test its functions. We carried out a survey (between 8 February to 31 March, 2021) to assess the overall need for an assessment tool as well as the usability of the IACT. Results: A total of 110 responses were received from different countries and practitioners' groups. The majority of the participants (86.11%) stated they would use a tool for AchB assessment if available and when they were asked to rate the IACT against other tools, amongst 34 responders, 20.59% rated it better and 8.82% rated it significantly better, 44.12% rated it neither better, nor worse, 14.71% rated it worse and 11.76% somewhat worse. Conclusion and Relevance: There is a need for an anticholinergic burden calculator to assess the anticholinergicity of medications. Tools such as the IACT potentially could meet this demand due its ability to assign scores to current and new medications appearing on the market based both on their chemical structure and reported adverse pharmacological effects. References and/or Acknowledgements: Conflict of Interest: No conflict of interest